Pemijahan Induk Ikan Gurami (Osphronemus GouramyLac) Kampar di Desa Sawah Baru Kecamatan Kampa, Kabupaten Kampar - Aryani, Netti; Hasibuan, Saberina; Fajri, Nur El; Suharman, Indra; Asiah, Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
A group of farmers in Sawah Baru Village work at the Kampar Gurami fish hatchery. The Pulai Jaya farmer group used natural techniques for gouramy spawning in the hatchery activities. Due to insufficient spawning eggs and intermittent seed production, this group has a challenge that results in very little revenue from its operations. The following goals of community service projects are : 1) Transfer technology for semi-natural gourami spawning to a farmer group in Pulai Jaya so they can produce more kampar gourami seeds. 2) Raise the revenue of the Pulai Jaya Farmers chairman and members and generate jobs, 3) In Sawah Baru Village, information agents and skills about the hatchery technology for semi-natural Kampar Gourami are being developed in order to be shared with other villages. The chairman and members of the Pulai Jaya farmer group have been motivated once again to carry out seeding activities as a result of this activity, according to the findings of observations made of them. They can also effectively absorb and put to use the provided information.